Do the Autism Spectrum Quotient (AQ) and Autism Spectrum Quotient Short Form (AQ-S) Primarily Reflect General ASD Traits or Specific ASD Traits? A Bi-Factor Analysis. (June 2017) - Murray, Aja Louise; McKenzie, Karen; Kuenssberg, Renate; Booth, Tom
In the current study, we fit confirmatory bi-factor models to the items of the Autism Spectrum Quotient (AQ) and Autism Spectrum Quotient Short Form (AQ-S) in order to assess the extents to which the items of each reflect general versus specific factors. The models were fit in a combined sample of individuals with and without a clinical diagnosis of autism spectrum disorders. Results indicated that, with the exception of the Attention to Details factor in the AQ and the Numbers/Patterns factors in the AQ-S, items primarily reflected a general factor. This suggests that when attempting to estimate an association between a specific symptom measured by the AQ or AQ-S and some criterion, associations will be confounded by the general factor. To resolve this, we recommend using a bi-factor measurement model or factor scores from a bi-factor measurement whenever hypotheses about specific symptoms are being assessed.